Relationship Between Age And Knowledge of Mothers on Early Weaning In The Working Area of The Muara Fajar Health Center - Yusmaharani; Ratih, Rini Hariani; Nurmaliza (JIM - Journal International Multidisciplinary, 2023)
Breast milk is very important for the growth of babies, because it can increase antibodies and prevent stunting. Breastfeeding can be given until the baby is 2 years old. The purpose of this study was to find out whether there is a relationship between age and mother's knowledge of early weaning in the working area of ​​the Muara Fajar Health Center. This study used a cross sectional study approach. The population in this study were mothers who had toddlers aged less than 3 years, sampling was carried out by accidental side to 47 respondents. Data analysis using chi square. Statistical test results showed that there was no relationship between age and early weaning (P = 0.965 > 0.05), there was a relationship between knowledge and early weaning (P = 0.018 <0.05), odds ratio/OR = 0.186 meaning mothers who had knowledge lack of early weaning 0.186 times.